Le Grand Paris: Quels outils, quels enjeux? - André De Palma (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
– The purpose of this Round Table is to assess the economic effects of major transport infrastructure projects. The term "major projects" is used to designate qualitative leaps, be it the mapping out of new road or rail rings to link disparate radial penetration routes or the introduction of more-targeted innovations tackling frequency, speed or automation. (...)
Keywords: 330